A comparative study of combination of Myo-inositol and D-chiro-inositol versus Metformin in the management of polycystic ovary syndrome in obese women with infertility - Sujana Thalamati (Publishing House TRILIST, 2020)
Polycystic ovary syndrome (PCOS) is a symptom complex associated with increased amounts of circulating androgens in females, increased insulin resistance and obesity. The drugs, Myo-inositol, D-chiro-inositol and Metformin, which are insulin sensitizers, are very helpful in taking care of one of the key components of PCOS that is insulin resistance. Myoinositol and D-chiro-inositol are isomeric forms of inositol that have insulin-like properties, acting as second messengers in the insulin intracellular pathway; both of these molecules are involved in the increasing insulin sensitivity of different tissues to improve metabolic and ovulatory functions. This study was done to compare the effects of combination of Myo-inositol and D-chiro-inositol with the use of metformin on clinical and biochemical profile in PCOS. Methods. A prospective, randomized, comparative study was conducted on 200 patients. The patients were randomly assigned into the two groups of 100 each. Group A receiving Tab. Myoinositol 550mg twice daily and Tab. D-chiro-inositol 13.8mg twice daily and Group B receiving Tab. Metformin 500mg thrice daily. The patients were assessed by menstrual cycle regulation, hirsutism score (Ferriman Gallwey), fasting and postprandial glucose and insulin levels, serum dehydroepiandrosterone levels, serum free testosterone levels and serum luteinizing and follicle stimulating hormone ratio. Results. In both the groups there was significant improvement in all the above mentioned parameters, however the group with Combination of Myo-inositol and D-chiro-inositol had statistically significant improvement over the Metformin group. Conclusions: Combination of Myo-inositol and D-chiro-inositol and use of metformin, significantly improved insulin sensitivity in PCOS women. But combination of Myo-inositol and D-chiro-inositol was effective in controlling the hormonal profiles (luteinizing/follicle stimulating hormone ratio and free testosterone) when compared to Metformin.